Optimalisasi Layanan Program Unggulan Pendidikan Agama Islam Dalam Pembelajaran Kelas di SDN Nglawak 1 Kecamatan Kertosono Nganjuk - Rohmawati, Siti Nur; Masyhadi (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2025)
Optimizing services is very important in developing superior school programs. One of them is a superior program in the field of Islamic religious education. This superior program is able to improve learning outcomes for students. The aims of this research are, 1) To analyze how PAI's superior program services are managed in learning at SDN Nglawak 1, Kertosono Nganjuk District., 2) To analyze PAI's superior program for learning at SDN Nglawak 1, Kertosono Nganjuk District., 3) To analyze improvements PAI's flagship program in learning at SDN Nglawak 1, Kertosono Nganjuk District. Meanwhile, the type of research used in this research is qualitative research with a research approach in the form of a case study research approach at SDN Nglawak 1, Kertosono Nganjuk District. The results of this research are, First, In the process of optimizing the management of program services, SDN Nglawak 1 Kertosono divides the responsibility for implementation into three areas, namely: the curriculum sector, the student sector and the infrastructure sector. Each deputy head is responsible for implementing the program. The curriculum at SDN Nglawak 1 Kertosono is a combination of the government curriculum and the Islamic boarding school curriculum. The superior programs that are being promoted are 1) dhuha prayers in congregation (SHOIDHUBER), 2) muroja'ah every Friday together (MUJUMBER), 3) Friday giving and sharing, 4) learning to read Asmaul Husna and memorizing juz every time 30, 5) start and finish learning to read sholawat busyro, thibil qulub and others. Obstacles in implementation arise including the diversity of students with different social backgrounds. The principal of SDN Nglawak 1 Kertosono always carries out evaluations consisting of evaluating program implementation and evaluating program achievements. Evaluation of program implementation is carried out by holding regular meetings between school leaders and the teacher council, as well as by asking for feedback from student parents. Evaluation of program achievements is carried out through learning results tests and observations of student behavior and attitudes. Second, school services that are encouraged to support the success of school programs are identifying target audiences and introducing superior programs. Schools can determine what media will be used for messages to be conveyed to the target audience. Meanwhile, the superior programs offered by schools use integration between the Islamic boarding school curriculum and the national curriculum